2017
DOI: 10.15746/sms.17.007
|View full text |Cite
|
Sign up to set email alerts
|

Four Consecutive Recurrent Abortions in Patient with Essential Thrombocythemia

Abstract: Essential thrombocythemia (ET) is characterized by most cases in which platelet counts exceed 1 million/μL. ET is usually no symptoms during non-pregnancy, but arterial and venous thrombosis and hemorrhage may develop in pregnancy. Pregnancy in these patients is associated with many complications in both pregnant women and fetuses such as recurrent abortion, intrauterine fetal growth restriction, preterm delivery, preeclampsia, and stillbirth. In these patients, aspirin, low-molecular-weight heparin (LMWH), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…ET in pregnant women was reported to increase the risk of abortion by 3-fold, and many pregnant ET patients are asymptomatic. [6] Published reviews have reported live birth rates of 50% to 70% and spontaneous abortion rates of 25% to 50% in pregnancy with ET. [7,8] Placental micro-infarctions due to the increased platelet number and placental damage from autoantibodies are among the underlying pathological basis of first trimester abortion in ET patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ET in pregnant women was reported to increase the risk of abortion by 3-fold, and many pregnant ET patients are asymptomatic. [6] Published reviews have reported live birth rates of 50% to 70% and spontaneous abortion rates of 25% to 50% in pregnancy with ET. [7,8] Placental micro-infarctions due to the increased platelet number and placental damage from autoantibodies are among the underlying pathological basis of first trimester abortion in ET patients.…”
Section: Discussionmentioning
confidence: 99%
“…[7,8] Placental micro-infarctions due to the increased platelet number and placental damage from autoantibodies are among the underlying pathological basis of first trimester abortion in ET patients. [6] The detrimental effects of ET on pregnant women and fetuses are mostly microcirculation disturbances, thromboembolic disease, and bleeding tendencies in rare cases. The clinical manifestations of ET in these patients include not only spontaneous abortion but also premature delivery and fetal growth retardation.…”
Section: Discussionmentioning
confidence: 99%